Cultural competence in healthcare professionals, specialised in diabetes, working in primary healthcare—A descriptive study. (18th June 2021) - Pettersson, Sara; Holstein, Jane; Jirwe, Maria; Jaarsma, Tiny; Klompstra, Leonie
Abstract: Self‐care is the most important cornerstone of diabetes treatment. As self‐care is affected by cultural beliefs, it is important for healthcare professionals to be able to adapt their educational approach and to be culturally competent. The aim of this study was to describe the cultural competence in Swedish healthcare professionals, specialised in diabetes care and to examine related factors for cultural competence. The healthcare professionals' perceived level of cultural competence was measured across three domains—Openness and awareness, Workplace support and Interaction skills—in 279 Swedish healthcare professionals from all 21 regions of Sweden, using the Cultural Competence Assessment Instrument (Swedish version—CCAI‐S). Descriptive statistics were used to describe cultural competence in healthcare professionals, and linear regression was conducted to examine factors related to cultural competence. Of the healthcare professionals studied, 58% perceived that they had a high level of Openness and awareness, 35% perceived that they had a high level of Interaction skills and 6% perceived that they had a high level of Workplace support. Two factors were found to be related to cultural competence, namely, high percentage of migrant clients at the healthcare clinic and whether the healthcare professionals previously had developed cultural competence through practical experience, education and/or by themselves. In conclusion, most healthcare professionals perceived that they had cultural openness and awareness but need more support from their workplace to improve their interaction skills. Cultural competence‐related education could support the healthcare professionals to develop interaction skills.